Two-beam laser purification of quartz raw material - V. A. Emelyanov; E. B. Shershnev; S. I. Sokolov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The paper presents a numerical simulation of laser separation under the influence of laser beams with wavelengths  of  10.6  microns  and  1.06  microns  on  quartz  raw  material  used  in  the  electronics  industry in  the  manufacture  of  photomasks.  The  temperature  fields  obtained  by  the  finite  element  method  and the analytical solution are compared. The temperature distribution to a depth of 50 microns is almost the same when using both methods of solution, while with increasing depth the temperature difference increases by 10 %, which allows using both methods of solution, since in practice the temperature distribution in the near-surface layers,  which  determines  the  formation  of  agglomerates  with  impurity  inclusions,  is  more  important. It  is  revealed  that  the  efficiency  of  separation  of  quartz  raw material  depends  on  the  processing  speed  and the energy properties of laser radiation, which allows to choose the optimal processing parameters that ensure the effective formation of agglomerates containing impurity inclusions. Experimental studies of bi-beam laser cleaning  of  quartz  raw  material  were  carried  out,  which  allowedus to determine the optimal processing parameters of quartz raw material for effective cleaning of it from impurity inclusions, that make it possible to manufacture photomasks used in the production of microcircuits with improved performance characteristics.